On the endemic spider species of the genus Savigniorrhipis Wunderlich, 1992 (Araneae: Linyphiidae) in the Azores (Portugal), with description of a new species - Crespo, Luís Carlos; Bosmans, Robert; Cardoso, Pedro; Borges, Paulo A.v. (Zootaxa, 2013)
Savigniorrhipis topographicus new species is described from the Azores. The synapomorphies of Savigniorrhipis are discussed along with the affinities of the genus within the Savignia-group. Given the extremely restricted and increasingly disturbed habitat, S. topographicus new species should be classified as Critically Endangered and its single forest habitat at Topo (São Jorge Island) should increase its current protection level to a strict nature reserve.